Visualizing Preosteoarthritis: Updates on UTE‐Based Compositional MRI and Deep Learning Algorithms - Sun, Dong; Wu, Gang; Zhang, Wei; Gharaibeh, Nadeer M.; Li, Xiaoming (Journal of magnetic resonance imaging, 2025)
Osteoarthritis (OA) is heterogeneous and involves structural changes in the whole joint, such as cartilage, meniscus/labrum, ligaments, and tendons, mainly with short T2 relaxation times. Detecting OA before the onset of irreversible changes is crucial for early proactive management and limit growing disease burden. The more recent advanced quantitative imaging techniques and deep learning (DL) algorithms in musculoskeletal imaging have shown great potential for visualizing “pre‐OA.” In this review, we first focus on ultrashort echo time‐based magnetic resonance imaging (MRI) techniques for direct visualization as well as quantitative morphological and compositional assessment of both short‐ and long‐T2 musculoskeletal tissues, and second explore how DL revolutionize the way of MRI analysis (eg, automatic tissue segmentation and extraction of quantitative image biomarkers) and the classification, prediction, and management of OA. Plain Language Summary Detecting osteoarthritis (OA) before the onset of irreversible changes is crucial for early proactive management. OA is heterogeneous and involves structural changes in the whole joint, such as cartilage, meniscus/labrum, ligaments, and tendons, mainly with short T2 relaxation times. Ultrashort echo time‐based magnetic resonance imaging (MRI), in particular, enables direct visualization and quantitative compositional assessment of short‐T2 tissues. Deep learning is revolutionizing the way of MRI analysis (eg, automatic tissue segmentation and extraction of quantitative image biomarkers) and the detection, classification, and prediction of disease. They together have made further advances toward identification of imaging biomarkers/features for pre‐OA. Level of Evidence 5 Technical Efficacy Stage 2